The Grano de Oro plateau (Moravia, Chirripó): a tectonic damming basin in Alta Talamanca, Costa Rica - Calvo, Cristian; Salazar, Mónica; Alfaro, David; Fregni, Sebastián; Alvarado, Guillermo E. (Revista geológica de América central, 2021)
The Grano de Oro plateau has an average altitude of 1,100 m a.s.l. and an area of ⁓5.5 km2, it is a morphological anomaly in the Talamanca mountain range, with particular morphostructural and fluvial sedimentology characteristics. It consists of an exorheic basin in which a floodplain predominates with typical geoforms and lithofacies. Its deposits are mainly distributed along the fluvial axis of the Moravia River and within the geoforms of the meandering fluvial system are recognized: terraces, sand bars, channels, lakes, among others. A genesis model is proposed for the basin where the geometry and kinematics of the Alcantarilla fault, to the NW of the plateau, cause a transpressive regime and a positive flower structure, tilting the structural block to the E of the altiplano, damming the Moravia River. The Alcantarilla fault is probably neotectonic, due to the presence of seismicity and the age of the deposits in the basin. The geoforms and sediments observed are young and present a high and variable evolution due to the permanent modeling of the postglacial landscape (since the Greenlandian) directly related to mild active tectonics and alterations from human intervention, which influence the fluvial dynamics in the territory.